2018
DOI: 10.1093/milmed/usy013
|View full text |Cite
|
Sign up to set email alerts
|

Has Current French Training for Military Orthopedic Surgeons Deployed in External Operations Been Appropriately Adapted?

Abstract: The large variety and technical nature of the performed operations requires the training of highly qualified military orthopedic surgeons with both experience in war surgery and management of after-effects and complications. Orthopedists are also required to carry out procedures dealing with neurosurgery, general, and/or vascular surgery on missions. These data highlight the complexity of military surgeons' training along with the hyper-specialization of the civilian medical world. For more than 10 yr, French … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Lectures, discussions, role-playing, ’hands-on’ basic skills training, materials, videos and simulations were used as in-person modalities. Additionally, 9 studies [ 27 , 84 , 86 , 90 , 118 , 225 , 264 , 298 , 308 ] suggested a professional approach (such as Masters degrees and postgraduate studies in universities) as a way of preparing healthcare workers for health emergencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lectures, discussions, role-playing, ’hands-on’ basic skills training, materials, videos and simulations were used as in-person modalities. Additionally, 9 studies [ 27 , 84 , 86 , 90 , 118 , 225 , 264 , 298 , 308 ] suggested a professional approach (such as Masters degrees and postgraduate studies in universities) as a way of preparing healthcare workers for health emergencies.…”
Section: Resultsmentioning
confidence: 99%
“…On training methods, 68 studies [ 13 17 , 20 25 , 27 30 , 32 , 33 , 37 , 41 , 45 , 47 , 48 , 53 , 58 , 59 , 62 , 65 , 68 , 79 , 84 , 85 , 87 , 88 , 90 , 93 , 97 , 111 , 123 125 , 138 , 141 , 145 , 146 , 148 , 153 , 161 , 167 , 168 , 170 , 193 , 204 , 214 , 216 , 247 , 251 , 255 , 261 , 294 , 297 , 298 , 300 , 304 , 313 , 321 , 322 …”
Section: Prominent Topic Areasunclassified
“…The curriculum is more and more determined by early hyperspecialisation, with little possibility of experiencing other surgical specialties, even within or related to the chosen specialty. Thus, deployments, which may require broader medical expertise, necessitate an additional level of preparedness among young military surgeons 3 4 8–10. The supplementary education can include compulsory additional training under the aegis of the Val-de-Grâce School for two semesters outside the specialty, extra-curricular courses (Advanced Course for Deployment Surgery; ACDS11 and ATLS)12 and a fellowship abroad.…”
Section: Introductionmentioning
confidence: 99%